Lung cancer incidence among world trade center rescue and recovery workers - Keith Sigel; Rafael E. de laHoz; Steven B. Markowitz; Chung Yin Kong; Kimberly Stone; Andrew C. Todd; Juan P. Wisnivesky (Cancer Medicine, 2022)
Abstract Background Many World Trade Center disaster (WTC) rescue and recovery workers (WTC RRWV) were exposed to toxic inhalable particles. The impact of WTC exposures on lung cancer risk is unclear. Methods Data from the WTC Health Program General Responders Cohort (WTCGRC) were linked to health information from a large New York City health system to identify incident lung cancer cases. Incidence rates for lung cancer were then calculated. As a comparison group, we created a microsimulation model that generated expected lung cancer incidence rates for a WTC‐ and occupationally‐unexposed cohort with similar characteristics. We also fitted a Poisson regression model to determine specific lung cancer risk factors for WTC RRWV. Results The incidence of lung cancer for WTC RRWV was 39.5 (95% confidence interval [CI]: 30.7–49.9) per 100,000 person‐years. When compared to the simulated unexposed cohort, no significant elevation in incidence was found among WTC RRWV (incidence rate ratio [IRR] 1.34; 95% CI: 0.92–1.96). Predictors of lung cancer incidence included age, smoking intensity, and years since quitting for former smokers. In adjusted models evaluating airway obstruction and individual pre‐WTC occupational exposures, only mineral dust work was associated with lung cancer risk (IRR: 2.03; 95% CI: 1.07–3.86). Discussion In a sample from a large, prospective cohort of WTC RRWV we found a lung cancer incidence rate that was similar to that expected of a WTC‐ and occupationally‐unexposed cohort with similar individual risk profiles. Guideline‐concordant lung cancer surveillance and periodic evaluations of population‐level lung cancer risk should continue in this group.